Buckling resistance and its effect on the gas barrier of composite coating layers based on polyvinyl alcohol and montmorillonite - Zainal Abedin, Nur Hanani; Schiessl, Stefan; Langowski, Horst Christian (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
In addition to the mechanical properties and barrier performance, one of the key properties of flexible films used in food packaging is the resistance of their gas barrier layer to buckling and bending. Testing the gas barrier before and after mechanical stress is time-consuming and resource-intensive, but important to assure a certain gas barrier during the whole life time of the package until food consumption. The aim of this study was, on the one hand, to identify the most significant influencing factors of a composite lacquer formulation and coating on its buckling resistance and, on the other hand, to show a fast and efficient method to identify defects occurring during buckling. The influence of mechanical stress was simulated via Gelbo-Flex treatment, and the samples were examined and evaluated before and after using light microscopy. The evaluation was verified with scanning electron microscopy (SEM) and helium barrier measurement. Polyethylene terephthalate (PET) and polyethylene (PE) films were coated with composite barrier lacquers made of polyvinyl alcohol (PVA) and montmorillonite (MMT) and the wet coating layer thickness (20, 40, 80, and 130 μm) and the composition of the coating were changed. It was found that thin coatings are more resistant to buckling than thick coatings. It was also shown that a higher proportion of MMT in the coating layer leads to a better gas barrier, but poorer buckling resistance. Additionally, it was found that soft PE films are already subjected to high stresses during the coating process, which means that barrier coatings do not build up ideally. However, the barrier-coated soft film withstood mechanical stress better and lost less barrier by a lower factor than the counterpart on the basis of PET. To conclude, the evaluation of the buckling resistance with microscopy offers an efficient method during lacquer development; however, the final decision on the right lacquer composition is dependent on many factors.